Crystallisation of ferrous sulphate heptahydrate: Experiments and modelling. (7th December 2011) - Shaikh, Latif; Pandit, Aniruddha; Ranade, Vivek
Abstract Crystallisation is an industrially important unit operation for purifying and separating chemical mixtures. A generic crystallisation modelling framework has been implemented in the general process modelling system (gPROMS) software (of PSE, UK). This framework can be used to model the batch cooling crystallisation of ferrous sulphate heptahydrate (FSH). The parameter estimation and sensitivity of the predicted results with various numerical parameters was studied for batch crystalliser. An Excel "front‐end" to the gPROMS model was developed to facilitate the interactive use of the model. © 2011 Canadian Society for Chemical Engineering